Synthesis and Characterization of Conductive Polypyrrole: The Influence of the Oxidants and Monomer on the Electrical, Thermal, and Morphological Properties - Abdirahman Yussuf; Mohammad Al-Saleh; Salah Al-Enezi; Gils Abraham (International Journal of Polymer Science)
Conductive polymer, polypyrrole (PPy), was synthesized by chemical oxidative polymerization technique for a period of four hours at room temperature using pyrrole monomer (mPPy) in aqueous solution. Different oxidants such as ferric chloride (FeCl3) and ammonium persulphate (N2H8S2O8) and surfactant sodium dodecyl sulphate (C12H25NaO4S) were used. The produced PPy samples were characterized by using different techniques such as the electrical resistivity by four probe technique, thermogravimetry analysis (TGA), differential scanning calorimetry (DSC), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy (SEM). The performance of the oxidants has been investigated and compared. It was found that both oxidants, FeCl3 and N2H8S2O8, have decreased electrical resistivity as a function of temperature, which means increased conductivity. However, FeCl3 has achieved better performance than N2H8S2O8, where it has achieved a lower resistivity of about 60 ohms at room temperature, which indicates higher conductivity of PPy samples with FeCl3 as an oxidant. Similarly, further investigation of FeCl3 oxidant has been conducted by varying its concentration, and its influence on the final properties was reported. It has been observed that the morphology of PPy samples has a significant influence on the conductivity. It was found that 0.1 M and 0.05 M concentrations of FeCl3 oxidant and monomer, respectively, have achieved better thermal stability, which is FeCl3/mPPy ratio of 2 as an optimum value. FTIR and XRD results confirmed the structural formation of polypyrrole from pyrrole monomer during the synthesizing process.